2022
DOI: 10.32604/phyton.2022.020721
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Etiology, Molecular Genetics and Management Perspectives of Northern Corn Leaf Blight of Maize (Zea mays L.)

Abstract: Maize is cultivated extensively throughout the world and has the highest production among cereals. However, Northern corn leaf blight (NCLB) disease caused by Exherohilum turcicum, is the most devastating limiting factor of maize production. The disease causes immense losses to corn yield if it develops prior or during the tasseling and silking stages of crop development. It has a worldwide distribution and its development is favoured by cool to moderate temperatures with high relative humidity. The prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…Similarly, the NLB is favoured by mild temperatures (15–25°C), high relative humidity (90%–100%), extended periods of leaf wetness, and frequent light showers as noticed by Ogliari et al (2007). It had also been reported that the distribution and development of NLB is favoured by long dew periods, and cool to moderate temperatures with high relative humidity across maize‐growing areas of the world (Ahangar et al, 2022; Badu‐Apraku et al, 2021). Hence, extreme impact of leaf blight on maize in the mid‐ and high‐land agro‐ecologies of Uganda, Kenya, Ethiopia, Zambia and South Africa have been reported (Ramathani et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, the NLB is favoured by mild temperatures (15–25°C), high relative humidity (90%–100%), extended periods of leaf wetness, and frequent light showers as noticed by Ogliari et al (2007). It had also been reported that the distribution and development of NLB is favoured by long dew periods, and cool to moderate temperatures with high relative humidity across maize‐growing areas of the world (Ahangar et al, 2022; Badu‐Apraku et al, 2021). Hence, extreme impact of leaf blight on maize in the mid‐ and high‐land agro‐ecologies of Uganda, Kenya, Ethiopia, Zambia and South Africa have been reported (Ramathani et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Such environmental conditions may support sporulation and conidia germination, infection, establishment and development of NLB in maize. Other studies also reported that epidemic of NLB is influenced by weather variables, among other factors (Ahangar et al, 2022;Badu-Apraku et al, 2021;Camera et al, 2019;Wathaneeyawech et al, 2015).…”
Section: Independent Variable Dfmentioning
confidence: 93%
See 3 more Smart Citations